Diffusion-weighted magnetic resonance imaging using 3D MOSAIC segmentation and 3D navigator phase correction - Jezzard, P; Frost, R; Miller, K; Porter, D (United States Patent and Trademark Office, 2014)
In a magnetic resonance apparatus and operating method therefore, 3D navigator data are acquired and are used to correct spatially varying phase errors in contemporaneously acquired imaging data in each shot of a multi-shot data acquisition sequence. A mosaic sampling scheme is used to enter the diffusion-weighted magnetic resonance data and the navigator data into k-space respectively in blocks that each form a subset of the entirety of k-space. The navigator data in each shot are entered into a block that is located at the center of k-space, and, in each shot, the corresponding image data are entered into an offset block in k-space, that is offset in at least one spatial direction from the navigator data block. The offset is varied from shot-to-shot.